1997
DOI: 10.1023/a:1026333222008
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 1. The monoamines dopamine (DA), norepinephrine (NE), epinephrine (E), and serotonin (5-HT) serve as endogenous neurotransmitters in the nervous system. We recently reported that the neurotransmitter DA can trigger apoptosis (programmed cell death; PCD) in cultured, postmitotic chick embryo sympathetic neurons, suggesting a role for apoptosis in degenerative processes such as Parkinson's disease (PD). However, PD is also associated with involvement of other monoaminergic (MA) neuronal systems (noradrenergic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In support of this concept, we recently showed that DA can induce apoptosis in cultured neuronal as well as non-neuronal cells, including chick embryo sympathetic neurons, mouse thymocytes, and rat pherochromacytoma cells (PC12) (7)(8)(9)(10). Based on these findings we hypothesized that neuronal degeneration in PD may be caused at least in part by DA-mediated induction of apoptosis in the nigrostriatal neurons.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In support of this concept, we recently showed that DA can induce apoptosis in cultured neuronal as well as non-neuronal cells, including chick embryo sympathetic neurons, mouse thymocytes, and rat pherochromacytoma cells (PC12) (7)(8)(9)(10). Based on these findings we hypothesized that neuronal degeneration in PD may be caused at least in part by DA-mediated induction of apoptosis in the nigrostriatal neurons.…”
mentioning
confidence: 86%
“…Paravertebral sympathetic ganglia at embryonic day 9 (8,24) were dissected out, and the cells were dissociated by trypsinization (0.25% in EDTA for 30 min at 37°C). Cells were then plated on 24 poly-L-lysine-coated wells (4 ϫ 10 5 cells/well) or 35-mm tissue culture plates (10 6 cells/well) (TPP, Trasadingen, Switzerland) and grown in serum-free medium DCCM-1 (Biological Industries, Kibbutz Beit Haemek, Israel) supplemented with 2% chick embryo extract, 0.5% horse serum, 20 g/ml fluorodeoxyuridine, and 20 g/ml uridine (to kill the non-neuronal cells), 2 mM glutamine, penicillin, streptomycin, and amphotericine B, and 10 ng/ml nerve growth factor (NGF).…”
Section: Cell Cultures and Da Treatmentmentioning
confidence: 99%
See 3 more Smart Citations